Characterization of the vastus lateralis torque-length, and knee extensors torque-velocity and power-velocity relationships in people with Parkinson's disease - Magris, Riccardo; Nardello, Francesca; Bombieri, Federica; Monte, Andrea; Zamparo, Paola (Frontiers in Sports and Active Living, 2024)
Introduction: Parkinson's disease (PD) is a prevalent neurodegenerative condition observed primarily in the elderly population that gives rise to motor and non-motor symptoms, one of which is muscle weakness. The aim of this study was to characterize the vastus lateralis torque-fascicle length (T-L) and the knee extensors torque-angular velocity (T-V) and power-angular velocity (P-V) relationships in PD patients and to investigate the influence of muscle geometry on muscle mechanics.Methods: Participants (11 PD: patients, 9 CR: age matched healthy controls; 10 CY: young healthy controls) performed: i) isometric contractions (e.g. MVC) to obtain the torque-angle and T-L relationships; ii) isokinetic (e.g. iso-velocity) contractions to obtain the T-V and P-V relationships.During the experiments, the architecture of vastus lateralis (pennation angle, fascicle length, muscle thickness) was also determined by using an ultrasound apparatus.Results: Significant differences were observed between PD patients and physically matched control groups (CR and CY) in terms of maximum isometric force (calculated as the apex of the T-L curve) and maximum mechanical power (apex of the P-V curve), but not in maximum shortening velocity.Among the mechanical variables investigated, mechanical power was able to identify differences between the less and the more affected side in PD patients, suggesting that this parameter could be useful for clinical evaluation in this population.The observed results cannot be explained by differences in muscle geometry at rest (similar in the three cohorts), but rather by the muscle capacity to change in shape during contraction, that is impaired in PD patients.